Bishop Melchisedec Ștefănescu (1823-1892) - lover of romanian books and culture (Confluenţe Bibliologice, 2020)
In the article the author writes about Melchisedec Stefanescu (1823-1892), leading ﬁgure of the age, participant in the Uniﬁcation of the Romanian, delegated in the Ad-hoc Divan in 1857. Melchisedec had a fruitful activity, culminating with his election in 1860 (even if for a very short term), as the Minister of Cults and Instruction in Kogalniceanu’s government. In 1860 he became Lieutenant of bishop at Husi, bishop of the new established Bishopric of the Lower Danube (1865) and Bishop of Roman (1879), where he will pastor until his death (16th May 1892). Another important moment of his career was gaining the dignity of being an active member of the Romanian Academy in 1870. He paid attention to the activities of libraries and considered „the issue of founding libraries as important as schools”. Melchisedec Stefanescu’s multilateral personality (scholar, priest and writer) was completed by that of a patriot. His role and involvement, far from being secondary, made possible the transition from tradition to modernity and progress.
Keywords: Melchisedec Ștefănescu (1823-1892); Library of the Romanian Academy